Two new sympatric species of Stenocercus (Squamata: Iguania) from the inter-Andean valley of the Mantaro River, Peru - Venegas, Pablo J.; Echevarría, Lourdes Y.; García-Ayachi, Luis A.; Landauro, Caroll Z. (Zootaxa, 2020)
We describe two new sympatric species of Stenocercus from the seasonally dry forest of the inter-Andean valley of the Mantaro River (Huancavelica department) in the Central Andes of central-southern Peru, at elevations of 1,693 to 2,920 m asl. Stenocercus diploauris sp. nov. is similar to S. formosus and S. ochoai, but differs in having a longitudinal neck fold and C-shaped nuchal mite pocket around the oblique fold and posteriorly limited by the antehumeral fold. Stenocercus nigrobarbatus sp. nov. is similar to S. frittsi and S. variabilis, however it can be distinguished by having a postfemoral mite pocket with one or more vertical folds or ridges and by the presence, in adult males, of a continuous black patch covering the infralabials, throat, chest, ventral surfaces of forelimbs, belly (as a midventral line), ventral surfaces of hind limbs, and pelvic region.